2013
DOI: 10.1186/1756-0500-6-275
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin suppresses inflammation by reducing ERK1/2 phosphorylation and NF kappa B activation in Leptin-induced Human Umbilical Vein Endothelial Cells (HUVECs)

Abstract: BackgroundHigh concentrations of plasma leptin and the release of pro-inflammatory cytokines in leptin-resistance in obesity have been reported to trigger endothelial dysfunction. The objective of this study was to elucidate the role of quercetin in modulating leptin-induced inflammation as assessed by the levels of Ob-Ra expression, ERK1/2 phosphorylation, NF-kappa B activation and TNF-alpha secretion in umbilical vein endothelial cells (HUVECs) in vitro.FindingsHUVECs were exposed to either control levels (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…It has been reported that Pin1 can regulate the activities of ERK, JNK, and NF-κB [3,9,12,13]. Meanwhile, these signal pathways play important roles in endothelial dysfunction [2,9,14,15]. However, it is yet unknown which is involved in Pin1-regulated vascular inflammation and atherosclerosis in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Pin1 can regulate the activities of ERK, JNK, and NF-κB [3,9,12,13]. Meanwhile, these signal pathways play important roles in endothelial dysfunction [2,9,14,15]. However, it is yet unknown which is involved in Pin1-regulated vascular inflammation and atherosclerosis in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the protective effects of this compound have been linked to its anti-inflammatory and/or antioxidant properties. In HUVEC cells, the negative effect of leptin addition on the expression of short chain leptin receptor isoform (Ob-Ra), ERK1/2 phosphorylation and NF-κ B activation was reduced by the addition of 125 µM quercetin, suggesting that the suppression of inflammation by quercetin may be of clinical relevance in the prevention of the diseases induced by leptin-resistant in obesity (Indra, Karyono, Ratnawati, & Malik, 2013). A similar anti-inflammatory effect of quercetin has been shown in macrophages, which infiltrate white adipose tissue, contributing to the chronic inflammation observed in obese subjects.…”
Section: Quercetin and Obesitymentioning
confidence: 99%
“…It is also important to highlight the findings obtained by Indra et al . , in which the administration of quercetin, a flavonol found in many fruits, produced an overexpression of LepRa in HUVEC cells. This finding is very important due to the involvement of this receptor in the transport of leptin through the BBB.…”
Section: Food Compounds Useful For Counteracting Leptin Resistancementioning
confidence: 99%